2021
DOI: 10.51470/plantarchives.2021.v21.s1.273
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Β-Glucan Extracted From Saccharomyces Cereviseae and Candida Albicans

Abstract: β-glucan is a polysaccharide with β-glycosidic linkages and it's a major structural component of various yeast cells. The goal of this research was to focus on the characterization of β-glucan extracted from both types of yeasts (Saccharomyces cereviseae and Candida albicans).The extraction of β-glucan depend on acid-base hydrolysis method and the yield of β-glucan extracted from Saccharomyces cereviseae was 63.35gm (28.15%) while the yield of βglucan extracted from Candida albicans was 9.35gm (4.15%) from 225… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…The current study’s findings are consistent with those of Jameel and Yassein (2021) who extracted β-glucan utilizing a technique based on Alkaline-acidic extraction stages with (4.15%); also, the morphological characteristics of the C. albicans derived β-glucan powder recorded as yellow crystal particles. In addition, Al-Jumaiee et al (2019) reported a yield of 5.95% from 4 g of the same yeast.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The current study’s findings are consistent with those of Jameel and Yassein (2021) who extracted β-glucan utilizing a technique based on Alkaline-acidic extraction stages with (4.15%); also, the morphological characteristics of the C. albicans derived β-glucan powder recorded as yellow crystal particles. In addition, Al-Jumaiee et al (2019) reported a yield of 5.95% from 4 g of the same yeast.…”
Section: Discussionsupporting
confidence: 89%
“…The results of a study by Jameel and Yassein (2021) performed by SEM on the particles of conventional β-glucan demonstrated the existence of homogeneous, irregular aggregating generating irregular mass with cylindrical to round particles The findings of very few studies on SEM for β-glucan obtained from C. albicans showed that the particles of β-glucan obtained from C. albicans having an aggregation of booklet-like platelet having particle sizes ranging from 1.2 to 1.84 µm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation